Beeswax Alcohol Prevents Low-Density Lipoprotein Oxidation and Demonstrates Antioxidant Activities in Zebrafish Embryos and Human Subjects: A Clinical Study - Kyung-Hyun Cho; Seung-Hee Baek; Hyo-Seon Nam; Ashutosh Bahuguna; Luis Ernesto López-González; Iván Rodríguez-Cortina; José Illnait-Ferrer; Julio César Fernández-Travieso; Vivian Molina-Cuevas; Yohani Pérez-Guerra; Ambar Oyarzabal Yera; Sarahi Mendoza-Castaño (Current Issues in Molecular Biology, 2024)
Oxidative stress is one of the primary instigators of the onset of various human ailments, including cancers, cardiovascular diseases, and dementia. Particularly, oxidative stress severely affects low-density lipid & protein (LDL) oxidation, leading to several detrimental health effects. Therefore, in this study, the effect of beeswax alcohol (BWA) was evaluated in the prevention of LDL oxidation, enhancement of paraoxonase 1 (PON-1) activity of high-density lipid & protein (HDL), and zebrafish embryo survivability. Furthermore, the implication of BWA consumption on the oxidative plasma variables was assessed by a preliminary clinical study on middle-aged and older human subjects (n = 50). Results support BWA augmentation of PON-1 activity in a dose-dependent manner (10–30 μM), which was significantly better than the effect exerted by coenzyme Q10 (CoQ10). Moreover, BWA significantly curtails LDL/apo-B oxidation evoked by CuSO4 (final 0.5 μM) and a causes a marked reduction in lipid peroxidation in LDL. The transmission electron microscopy (TEM) analysis revealed a healing effect of BWA towards the restoration of LDL morphology and size impaired by the exposure of Cu2+ ions (final 0.5 μM). Additionally, BWA counters the toxicity induced by carboxymethyllysine (CML, 500 ng) and rescues zebrafish embryos from development deformities and apoptotic cell death. A completely randomized, double-blinded, placebo-controlled preliminary clinical study on middle- and older-aged human subjects (n = 50) showed that 12 weeks of BWA (100 mg/day) supplementation efficiently diminished serum malondialdehyde (MDA) and total hydroperoxides and enhanced total antioxidant status by 25%, 27%, and 22%, respectively, compared to the placebo-control and baseline values. Furthermore, the consumption of BWA did not exhibit any noteworthy changes in physical variables, lipid profile, glucose levels, and biomarkers pertinent to kidney and liver function, thus confirming the safety of BWA for consumption. Conclusively, in vitro, BWA prevents LDL oxidation, enhances PON-1 activity in HDL, and positively influences oxidative variables in human subjects.